MULTIPLE VARIATIONS OF BRANCHES OF ABDOMINAL AORTA : A CASE STUDY - H., Shivarama C.; Shivarama, Bhat; K., Shetty R.; R., Avadhani (Journal of Health and Allied Sciences NU, 2012)
Multiple variations of the branches of abdominal aorta were observed during a routine dissection of the abdominal region in a 66-yearold male cadaver in the Department of Anatomy, Yenepoya Medical College, Yenepoya University, Mangalore. In the present case, both the inferior phrenic arteries arise from the celiac trunk. Left gastric artery is originates directly from abdominal aorta higher then celiac trunk. An accessory hepatic artery arises from the superior mesenteric artery. An accessory left renal artery found originating from the abdominal aorta. Right testicular artery arises as anterior branch of abdominal aorta. Knowledge of these variations could help surgeons to identify and protect the branches of abdominal aorta during surgery.
Keywords: Abdominal aorta; celiac trunk; hepatic artery; phrenic artery; renal artery; variations